2018
DOI: 10.2174/1567205015666171212094229
|View full text |Cite
|
Sign up to set email alerts
|

Catechol-O-methyltransferase, Cognition and Alzheimer's Disease

Abstract: Better understanding of the role of COMT in cognitive processes in AD, as well as integration of neurobiological, genetic, genomic and epigenetic data, might help in developing new potential therapies of cognitive impairments and psychotic symptoms, characteristic features of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…We also found that brain EV are significantly loaded with higher levels of essential brain enzymes during the preclinical stage of the disease, which included protein-L-isoaspartate (D-aspartate) omethyltransferase (PCMT1), neuroendocrine convertase 2 (PCSK2), dihydropyrimidinase-like 2 (DPYLS2), and biliverdin reductase-A (BLVRA). All these enzymes have previously been implicated in AD [60][61][62][63]. We also observed that the levels of these enzymes in brain EV, albeit upregulated in preclinical AD, were significantly downregulated throughout the entire disease progression.…”
Section: Discussionsupporting
confidence: 69%
“…We also found that brain EV are significantly loaded with higher levels of essential brain enzymes during the preclinical stage of the disease, which included protein-L-isoaspartate (D-aspartate) omethyltransferase (PCMT1), neuroendocrine convertase 2 (PCSK2), dihydropyrimidinase-like 2 (DPYLS2), and biliverdin reductase-A (BLVRA). All these enzymes have previously been implicated in AD [60][61][62][63]. We also observed that the levels of these enzymes in brain EV, albeit upregulated in preclinical AD, were significantly downregulated throughout the entire disease progression.…”
Section: Discussionsupporting
confidence: 69%
“…Dopaminergic neurons are also closely associated with AD pathology, and several alterations in the dopaminergic system have been reported in AD patients (Burns et al, 2005;Rossato et al, 2009). Dopaminergic neurons in the prefrontal cortex participate in the formation of cognitive memory (Perkovic et al, 2018). Loss of dopaminergic neurons affects synaptic plasticity in hippocampal CA1 neurons in AD (Nobili et al, 2017).…”
Section: Selenok Selenot Selenos and Selenommentioning
confidence: 99%
“…2, COMT is known to influence synaptic plasticity and dopamine metabolism, both of which are associated with cognition. In this context, two point mutations (i.e., Val108Met and rs4680 -> Val158Met) in this gene were identified to be predictors of cognition scores in AD patients through independent studies [30,31]. Interestingly, the latter mutation along with rs4646312 in COMT has been associated with T2DM [32].…”
Section: Comorbidity In Ad and T2dm Explained By Mechanistic Bel Graphsmentioning
confidence: 99%